Diplomacy in the 21st century a brief introduction - Sharp, Paul 1953- (Routledge, Taylor & Francis Group, 2019)
"This book provides an introduction to the theory and practice of diplomacy and its vital role in an era of increasing international uncertainty. The work employs a distinctive 'diplomatic perspective' on international relations and argues that the experience of conducting diplomacy gives rise to a set of priorities: first, the peaceful resolution of disputes; second, the avoidance of unwanted conflict; and, third, the minimization of the intensity of violent conflict where it has become unavoidable. It argues that changes in the international system require a shift in priorities from the diplomacy of problem-solving by building institutionalized cooperation, to the diplomacy of managing relationships between people. Divided into three sections, the first examines what is meant when we talk about diplomacy, why we need diplomats, and the operations of the modern diplomatic system of states. The second discusses the 'three bads,' about which people generally worry: bad leaders, bad media, and bad followers. The idea of 'bad' is considered in terms of the moral character, professional competence, and the consequences of what people do for us. The final section discusses diplomacy and bad diplomats, reviewing what people can do to help themselves and the professionals be good diplomats. This book is intended as a primary text for courses in international diplomacy and as a supplementary text for courses on contemporary issues in international relations"--
Description based on print version record and CIP data provided by publisher
Keywords: Diplomacy; Diplomats; International relations